Distributed Quantum Fiber Magnetometry. Issue 7 (17th May 2019) - Maayani, Shai; Foy, Christopher; Englund, Dirk; Fink, Yoel
Abstract: Nitrogen‐vacancy (NV) quantum magnetometers offer exceptional sensitivity and long‐term stability. However, their use to date in distributed sensing applications, including remote detection of ferrous metals, geophysics, and biosensing, is limited due to the need to combine optical, microwave (MW), and magnetic excitations into a single system. Existing approaches have yielded localized devices but not distributed capabilities. In this study, a continuous system‐in‐a‐fiber architecture is reported, which enables distributed magnetic sensing over extended lengths. Key to this realization is a thermally drawn fiber that has hundreds of embedded photodiodes connected in parallel and a hollow optical waveguide that contains a fluid with NV diamonds. This fiber is placed in a larger coaxial cable to deliver the required MW excitation. This distributed quantum sensor is realized in a water‐immersible 90‐m‐long cable with 102 detection sites. A sensitivity of 63 ± 5 nT Hz −1/2 per site, limited by laser shot noise, is established along a 90 m test section. This fiber architecture opens new possibilities as a robust and scalable platform for distributed quantum sensing technologies. Abstract : A water‐immersible 90‐m‐long fully‐integrated fiber system is constructed, which allows distributed quantum magnetic sensing over large distances with a sensitivity of 63 nT Hz −1/2 . The fiber contains hundreds of embedded photodiodes connected in parallel and a hollow optical waveguide that contains a fluid with nitrogen‐vacancy diamonds. Applications include remote detection of ferrous metals, geophysics, and biosensing.